The importance of being "on the road" - Duarte, José (ELOPE (Ljubljana), 2015)
Road stories are significant cultural objects that ˝provide a ready space for the exploration˝ (Cohan and Hark 1997, 2) of different landscapes, contributing to the encounter of the traveller with him/herself or with the Other. These cultural encounters offer the opportunity both for inner reflection upon the nation in which the protagonists travel. Such is the case of the Whitman brothers in The Darjeeling Limited (2007, Wes Anderson), who embark on a journey in India, seeking spiritual enlightenment from the problems of the past. The confrontation with the foreign Other will not only put into perspective a changed notion of the Indian nation but also their true purpose in life. Based upon the idea of the transformative power of journeys, and considering The Darjeeling Limited as a road movie, this article analyzes the brothers' awakening as they travel deeper into the Indian landscape to emerge with a renewed sense of self.
Keywords: Anderson, Wes:The Darjeeling Limited; kinematografija; popotovanje; transformacija; zgodbe ceste